Descripción del mecanismo bioquímico de la biohidrogenación en el rumen de ácidos grasos poliinsaturados: una revisión (2013)
Hydrolysis of galactolipids, phospholipids, sulfolipids and triglycerides is the first step in ruminal lipid metabolism resulting in saturated, monounsaturated and polyunsaturated fatty acids. It has been reported recently that the mechanism of conjugated linoleic acid (C18:2 cis-9, trans-11, CLA) production is associated with a prototropic displacement and the synthesis of its isomer C18:2 trans-10, cis-12, involves oxidated flavin adenine dinucleotide (FAD). First, linoleic acid (C18:2 cis-9, cis-12, LiA) is converted to CLA by the action of cis-9, trans-11 octadecanoate reductase, then CLA converts to trans-vaccenic acid (C18:1 trans-11, TVA) with the final product being stearic acid. LiA is the precursor of both CLA and TVA and FAD is used as a cofactor in these processes. One of the conclusions of this review is that as the knowledge of the ruminal biohydrogenation process increases, opportunities for its application become available. The nutritional strategies to increase the concentration of bioactive fatty acids in both milk and meat are the more relevant.